Mickey Mouse Clubhouse. Mickey's big splash - Allwine, Wayne, 1947-2009.; Walt Disney Television Animation; Walt Disney Studios Home Entertainment (Firm); Buena Vista Home Entertainment (Firm) (Burbank, CA : Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2009)
It's the hottest day of the year and even Goofy's chicken noodle ice cream cone has melted into soup. So Mickey and his pals are cooling off at Star Lake. Pete's hosting a Hawaiian luau, and it just might be the best beach bash ever, but only if you can help the gang pick the right mouseketools to get the party started. You'll ride on a tide of fun with Mickey as you reel in a big, red Gooey fish, float above the clouds with Pluto in a giant soap bubble, and help Donald rescue a flock of lost ducks. Filled with music, excitement and magical surprises.
Donald's ducks -- Pluto's bubble bath -- Mickey goes fishing -- Pete's beach blanket luau.
Title from container.
"Playhouse Disney."
Special features: Fun in the sun with Mickey and the gang game.
Voice, Wayne Allwine.
TV-Y.
DVD, region 1, full screen (1.33:1); Dolby Digital surround, digitally mastered, NTSC.
Keywords: Mickey Mouse (Fictitious character) -- Juvenile films; Goofy (Fictitious character) -- Juvenile films; Friendship -- Juvenile films; Summer -- Juvenile films; Luaus -- Juvenile films; Animal rescue -- Juvenile films; Fantasy television programs; Action and adventure television programs; Children's television programs; Animated television programs; Television series; Video recordings for the hearing impaired; French language materials; Spanish language materials